Sequential pattern mining using personalized minimum support threshold with minimum items - Alias, Suraya; Razali, Mohd Norhisham; Tan, Soo Fun; Sainin, Mohd Shamrie (2011)
One of the challenges of Sequential Pattern Mining is finding frequent sequential patterns in a huge click stream data (web logs) since the data has the issue of a very low support distribution.By applying a Frequent Pattern Discovery technique, a sequence is considered as frequent if it occurs more than the minimum support (min sup) threshold value.The conventional method of assuming one min sup value is valid for all levels of k-sequence, may have an impact on the overall results or pattern generation. In this paper, a personalized minimum support (P_minsup) threshold with user specified minimum items or min_i is introduced. The P_minsup is generated for each k-sequence by analyzing the overall support pattern distribution of the click stream data; while the min_i value gives the user the flexibility to gain control on the number of patterns to be generated on the next k-sequence by using the top min_i items. This approach is then applied in the SPADE Algorithm using vector array as an extension from the previous method of using relational database and pre-defined threshold.The result from this experiment demonstrates that P_minsup with the complement of min_i value approach is applicable in assisting the process of determining the suitable threshold value to be used in detecting users' frequent k-sequential topics in navigating the World Wide Web (WWW).